2020
DOI: 10.3390/microorganisms8121888
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Glycomic Analyses to Direct CAZyme Discovery for the Tailored Degradation of Canola Meal Non-Starch Dietary Polysaccharides

Abstract: Canola meal (CM), the protein-rich by-product of canola oil extraction, has shown promise as an alternative feedstuff and protein supplement in poultry diets, yet its use has been limited due to the abundance of plant cell wall fibre, specifically non-starch polysaccharides (NSP) and lignin. The addition of exogenous enzymes to promote the digestion of CM NSP in chickens has potential to increase the metabolizable energy of CM. We isolated chicken cecal bacteria from a continuous-flow mini-bioreactor system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Birds were maintained in a sanitized facility, as one goal of the current study was to ascertain the impact of CM on the structure and function of the enteric microbiota. We observed that the diversity of the microbiota (Shannon’s index of ≈6.8) was comparative to that of ceca harvested from broilers in commercial production settings [ 35 ]. Moreover, the structure of the microbiota amongst broilers maintained in replicate housing enclosures was consistent, which indicated that the establishing a diverse cecal microbiota via the administration of bacteria from a donor bird was successful.…”
Section: Discussionmentioning
confidence: 99%
“…Birds were maintained in a sanitized facility, as one goal of the current study was to ascertain the impact of CM on the structure and function of the enteric microbiota. We observed that the diversity of the microbiota (Shannon’s index of ≈6.8) was comparative to that of ceca harvested from broilers in commercial production settings [ 35 ]. Moreover, the structure of the microbiota amongst broilers maintained in replicate housing enclosures was consistent, which indicated that the establishing a diverse cecal microbiota via the administration of bacteria from a donor bird was successful.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-treated wheat straw and resulting growth cultures were analyzed using HPAEC-PAD to determine which CAZymes induced the differential expression patterns between pre-treatment methods. Furthermore, the combination of MAPP, linkage analysis, and metagenomics has recently been used to determine the CAZymes responsible for the digestion of non-soluble polysaccharides in chickens—an approach highly portable to anaerobic digesters [ 224 ]. As the field of biofuels progresses, a multi-disciplinary approach will be needed to fine-tune and standardize methods to optimize production, as diversity in microorganisms in combination with feedstocks and feedstock pre-treatments can drastically alter saccharification and fermentation efficiencies.…”
Section: Glycomic and Multi-omic Integrationmentioning
confidence: 99%
“…The acetyl-mannosamine transferase GT26 was only present in clade III strains. Only three types of carbohydrate esterases (CEs) were identified across all C. innocuum strains, all involved in plant cell degradation, CE6 (acetyl xylan esterase), CE4 (chitin deacetylase), and CE9 ( N -acetylglucosamine 6-phosphate deacetylase) ( 62 , 63 ). Four carbohydrate-binding modules were also observed across all clades, including CBM66, part of the LPXTG cell wall anchor domain-containing protein that degrades fructoside residues in fructans, and CBM48, associated with the GH13 family of CAZymes responsible for degrading starches ( 64 ).…”
Section: Resultsmentioning
confidence: 99%